Transdisciplinary approach to accelerate the adoption of hybrid renewable energy systems through sustainable design - Babatunde, Olubayo; Akintayo, Busola; Ighravwe, Desmond; Olanrewaju, Oludolapo (Frontiers in Built Environment, 2025)
The inclusion of renewable energy in the global energy mix has emerged as one of the viable solutions for addressing energy demand and ensuring decarbonization of the energy sector. However, their proliferation faces various challenges related to decision making, optimization and design complexity that cuts across various disciplines. Hence, transitioning into renewable energy is a transdisciplinary subject integrating expertise from diverse fields, including engineering, environmental science, economics, political and social sciences. This study presents a review of transdisciplinary approach to accelerate the adoption of hybrid renewable energy systems through sustainable design. The review starts with a discussion on the sustainable design principles with emphasis on lifecycle assessments, modularity, and resilience to enhance hybrid renewable energy systems (HRES) efficiency and adaptability. Next, the study surveyed various optimization techniques that have been used in the sizing of HRES, including linear programming and metaheuristics approaches. Furthermore, the study reviewed multi-criteria methods that can be used in the evaluation and prioritization of optimal HRES obtained from the optimization techniques based on multiple attributes. Also, the study examined how spatial optimization can be used to improve the adoption of HRES. Finally, the study proposed a transdisciplinary framework which synthesizes various disciplines that can help in accelerating the adoption of Hybrid Renewable Energy Systems. It is expected that this approach would provide a robust approach to the widespread adoption of HRES technologies.